2007
DOI: 10.1371/journal.pone.0001172
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Reduction of Polymorphic Sequences (CRoPS™): A Novel Approach for Large-Scale Polymorphism Discovery in Complex Genomes

Abstract: Application of single nucleotide polymorphisms (SNPs) is revolutionizing human bio-medical research. However, discovery of polymorphisms in low polymorphic species is still a challenging and costly endeavor, despite widespread availability of Sanger sequencing technology. We present CRoPS™ as a novel approach for polymorphism discovery by combining the power of reproducible genome complexity reduction of AFLP® with Genome Sequencer (GS) 20/GS FLX next-generation sequencing technology. With CRoPS, hundreds-of-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(175 citation statements)
references
References 27 publications
2
163
3
2
Order By: Relevance
“…Although the crosses between tetraploid A. lyrata individuals confirmed presence of the expected SRK alleles known to be present in the parents, they also indicated some inaccuracy in allele calls in relation to barcodes; a number of alleles that were not in the parents were assigned to individuals from the crosses, sometimes at high read numbers (see Jørgensen et al, 2012). We concluded that this was due to tag switching between barcodes, as had been suggested from other studies (van Orsouw et al, 2007;Carlsen et al, 2012). Blank lanes (negative controls) also sometimes contained sequences matching known SRK alleles, again often at high read numbers.…”
Section: Clustering and Srk Genotyping Strategiessupporting
confidence: 75%
“…Although the crosses between tetraploid A. lyrata individuals confirmed presence of the expected SRK alleles known to be present in the parents, they also indicated some inaccuracy in allele calls in relation to barcodes; a number of alleles that were not in the parents were assigned to individuals from the crosses, sometimes at high read numbers (see Jørgensen et al, 2012). We concluded that this was due to tag switching between barcodes, as had been suggested from other studies (van Orsouw et al, 2007;Carlsen et al, 2012). Blank lanes (negative controls) also sometimes contained sequences matching known SRK alleles, again often at high read numbers.…”
Section: Clustering and Srk Genotyping Strategiessupporting
confidence: 75%
“…However, a majority of these techniques mainly reduce the number of repetitive sequences and are ineffective in the recognition and elimination of paralogues and homoeologues, which cause the detection of false-positive SNPs. Recently, computational SNP calling methods were developed that can drastically reduce the number of false SNPs resulting from the alignment of duplicated sequences and re-sequencing errors (Baird et al, 2008;Barbazuk et al, 2007;Gore et al, 2009;Van Orsouw et al, 2007). Hence, the availability of reference sequences, the application of genome complexity reduction techniques and NGS technologies coupled with post-re-sequencing computational treatment become important prerequisites for genome-wide detection of SNPs in complex genomes.…”
Section: Snp Markersmentioning
confidence: 99%
“…Discovered cross-specific polymorphisms can later be converted into any modern SNP genotyping assay Trebbi et al, 2011). For instance, technologies such as complexity reduction of polymorphic sequences (CRoPS™) (Van Orsouw et al, 2007) or restriction site associated DNA (RAD) (Baird et al, 2008) can be successfully applied to generate cross-specific SNPs . Depending on the organism, this approach may result in the validation of about 1000 robust cross-specific markers, which can be later combined with public SNPs and used for mapping.…”
Section: Mapping and Map-based Cloning Of Qtlmentioning
confidence: 99%
“…However, the complexity of plant genomes with many repetitive sequences presents a challenge to sequence alignment and SNP identification (Zou et al 2014). Fortunately, a variety of protocols such as RRS (reduced representation shotgun sequencing) (Altshuler et al 2000), CRoPS (complexity reduction of polymorphic sequences) (Van Orsouw et al 2007), RAD (restriction-site associated DNA) tag sequencing (Baird et al 2008), GBS (genotyping by sequencing) (Elshire et al 2011), and SLAF-seq (specific length amplified fragment-sequencing) (Sun et al 2013), have been established that enable the reduction of genome complexity. All protocols take advantage of restriction enzymes for avoiding repeat-rich sequences in genomes and increasing the abundance of low copy regions in sequencing libraries.…”
Section: Introductionmentioning
confidence: 99%